(untitled) (Modern Problems of Metallurgy, 2021)
A review of research in the field of modeling processes in metal during heat treatment and pressure treatment of metal and the effect of processing on the physical and mechanical properties of steel with a chemical composition of 0.59% C, 0.31% Si, 0.73% Mn. A mathematical model for calculating the physical and mechanical properties of steel in the process of hot plastic deformation has been developed. As a result of modeling, the following functions were obtained: the amount of deformation in the direction of the applied force divided by the initial length of the material. The coefficient of elongation of the material with the actual chemical composition at a temperature of 1250 ± 10 ° C, which was 0.32. In the laboratory, hot plastic deformation of the sample with a diameter of 31 mm and a height of 124 mm from the test ingot by deposition of 50% When comparing the values of the load applied to the GPA in the laboratory they have close values of 45 MPa. The microstructure of the studied laboratory smelting after GPA consists mainly of ferrito-perlite structure, areas with a rough lamellar structure of perlite were observed. The study of the dendritic structure showed the extraction of dendrites in the area of ½ radius and the central part, which confirms the favorable effect on the uniformity of the structure. This confirms the adequacy of the obtained model. In the future, the obtained results will be used to develop a model for calculating the change in physical and mechanical properties of the metal of the railway axis in the development of promising methods and modes of its GPA.